Palliative Approach To Improving The Quality Of Life Of Terminal Patients - Isrofah Isrofah; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
ABSTRACT The palliative approach is a comprehensive effort aimed at improving the quality of life of terminally ill patients through symptom management, psychological, social, and spiritual support. This study aims to analyze the effectiveness of the palliative approach in improving the quality of life of terminally ill patients. The research method used a quantitative approach with a cross-sectional design on 100 terminally ill patients in the palliative care unit. Data were collected using a quality of life questionnaire and analyzed using descriptive and inferential statistical tests. The results showed that patients who received a comprehensive palliative approach had higher quality of life scores than those who did not receive optimal intervention (p<0.05). It was concluded that the palliative approach plays a significant role in improving the quality of life of terminally ill patients. Keywords: Palliative, Quality of Life, Terminal Patients, Nursing